If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying A + 12 = 3A + -96 Reorder the terms: 12 + A = 3A + -96 Reorder the terms: 12 + A = -96 + 3A Solving 12 + A = -96 + 3A Solving for variable 'A'. Move all terms containing A to the left, all other terms to the right. Add '-3A' to each side of the equation. 12 + A + -3A = -96 + 3A + -3A Combine like terms: A + -3A = -2A 12 + -2A = -96 + 3A + -3A Combine like terms: 3A + -3A = 0 12 + -2A = -96 + 0 12 + -2A = -96 Add '-12' to each side of the equation. 12 + -12 + -2A = -96 + -12 Combine like terms: 12 + -12 = 0 0 + -2A = -96 + -12 -2A = -96 + -12 Combine like terms: -96 + -12 = -108 -2A = -108 Divide each side by '-2'. A = 54 Simplifying A = 54
| 3b-9=b+5 | | 30x+44=25x+99 | | 6(2/3×-10) | | (21x+6)*2=180 | | g(x)=x^2-3/4x-7/64 | | 9495.36=3.14x*12 | | 0.13-0.03(x+2)=-0.01(1-x) | | e-132/3=-19 | | -3(x+2)-5=-3x-11 | | 100-(5x+16)=5(x+8)+x | | 66x+110=1100 | | T^2-t/6-35/6=0 | | X^2+y=24 | | -4(2x+2)-2x+2=-26 | | 10d-6d+3d=7 | | 3x=5x-10x | | 3a-a-a+a=20 | | 2.5(b+87)=3212 | | 15=-15+8u | | -10j-13j+14j=18 | | -6x+5.8=23.8 | | 7/4y-5/6y | | 5x^2+10y^2=4 | | 10v-v-7v+v+3v=18 | | 3x-6y=-46.5 | | secx+2tanx=0 | | 1.2=1+k^6 | | D=R(100-x)/100 | | 1/3w=31/4 | | -37-(-48)= | | 4x+6=-10 | | 23x^2-29=0 |